Service Quality to Customer Satisfaction with Situational Leadership as Moderation (Case Study on Travel Agent) - Yuniarso, Ari; Setyorini, Albertha Dwi; Anggiani, Sarfilianty (E-Journal of Tourism; Volume 8 Number 2 (September 2021)DO - 10.24922/eot.v8i2.72592, 2021)
Covid-19 pandemic has become a major challenge for the movement of the Indonesian economy and the world. Not a few people who have to accept a pay cut policy, some are laid off for a while, and even have to lose their jobs. So that this situation is a slap in the face to various industries, especially the tourism sector. Especially for travel agents, they face many obstacles, such as dealing with passenger funds due to canceling travel due to the Covid-19 pandemic. The study was conducted by measuring the quality of service with customer satisfaction on travel agents in a pandemic condition. The method of determining the sample used in this study is the purposive sampling method. The analytical technique used is path analysis technique. The resulted from the service quality variables has no significant effect on customers satisfaction but the customers feel the satisfactory after they doing the trip with Bali Citra Kinawa Sentosa Travel agent supported.